Pemberdayaan Ibu Rumah Tangga Melalui Pelatihan Pengolahan Ikan Asap dan Ikan Kering di Desa Korleko - Fitriani, Laily; Dermawan, Awan; Dwiyanti, Septiana; Asri, Yuliana (Jurnal Pengabdian Perikanan Indonesia, 2025)
This community service program aims to empower housewives in Korleko Village through training in processing smoked and dried fish. Korleko Village has quite high fisheries potential but has not been optimally utilized. This activity is carried out in the form of technical and managerial training with a participatory approach. The results of this activity show an increase in the knowledge and skills of housewives in processing fishery products, as well as the potential for increasing family income. This training also encourages the formation of joint business groups as a form of program sustainability.